2014
DOI: 10.3390/nu6010261
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Two Human Milk Fortifiers on Clinical Outcomes in Premature Infants

Abstract: The use of human milk fortifiers (HMF) helps to meet the high nutritional requirements of the human milk-fed premature infant. Previously available powdered products have not met the protein requirements of the preterm infant population and many neonatologists add powder protein modulars to help meet protein needs. The use of powdered products is discouraged in neonatal intensive care units (NICU) due to concern for invasive infection. The use of a commercially available acidified liquid product with higher pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 24 publications
3
37
0
Order By: Relevance
“…The results of this study support the work recently published by Thoene et al, 23 who showed a significantly higher incidence of metabolic acidosis in infants receiving acidified liquid HMF as compared with powdered HMF. They also found that infants had better daily weight gain on powdered HMF despite higher enteral calories and protein in the liquid HMF group.…”
Section: Discussionsupporting
confidence: 94%
“…The results of this study support the work recently published by Thoene et al, 23 who showed a significantly higher incidence of metabolic acidosis in infants receiving acidified liquid HMF as compared with powdered HMF. They also found that infants had better daily weight gain on powdered HMF despite higher enteral calories and protein in the liquid HMF group.…”
Section: Discussionsupporting
confidence: 94%
“…Though, many contradictory statements are found in the literature concerning the nutritional value of the human milk and the impact of prematurity and other maternal associated factors on its macronutrients and energy levels [20][21][22][23][24][25] . However, in most studies, found in the literature, concerning the nutritional value of donor milk, it is stated that banked milk, after pasteurization process, does not contain sufficient protein, fat and energy levels to sustain adequately a LBW infant, as the pasteurization process decreases mostly fat and protein analogies [26][27] . Significant variation in human milk's macronutrients (protein, fat, carbohydrates) and energy, either being raw or pasteurized, is a barrier that needs to be exceeded, to fulfill the preterm infants' nutritional needs.…”
Section: Coping With the Controversial Nutritional Value Of The Humanmentioning
confidence: 99%
“…Raw mother's milk macronutrients and energy are analyzed periodically (two to three times a week). For donor banked milk, macronutrients' and energy's analysis is conducted as soon as the milk is pasteurized [14,16,27] . Our experience is that this feeding and fortification policy, when infants are fed with an exclusive targeted fortified human milk diet, results in improved neonatal outcomes at hospital discharge.…”
Section: Coping With the Controversial Nutritional Value Of The Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no primary literature that proves any particular mode of fortification has a direct effect for promoting NEC. Some small studies suggest that acidified liquid human milk fortifier (HMF) versus powdered HMF may lead to increased cases of NEC (27). More research needs to be done to provide more defined guidelines for enteral feeding practices and preventing the development of NEC.…”
Section: Enteral Feeding Techniquesmentioning
confidence: 99%